The therapeutic potential of CXC chemokine blockade in acute inflammation in the brain. - Anthony, D; Walker, K; Perry, V (Ashley Publications Ltd, 1999)
Mammalian neurones of the central nervous system (CNS) are terminally differentiated, and there is little endogenous capacity of the CNS to repair itself. Peripheral tissue injury, disease or infection results in a stereotypical inflammatory response to protect the host from pathogens and to promote tissue repair. However, collateral or 'bystander' damage is characteristic of any inflammatory response. Thus, it is apparent that the CNS has evolved mechanisms to regulate tightly the acute inflammatory response, and in particular to restrict the recruitment of neutrophils, in an attempt to protect itself from the potentially damaging consequences of inflammation in the brain. However, neutrophils are not always excluded from the brain. Indeed, they are found in large numbers in the brain parenchyma following traumatic lesions, stroke lesions, and in rodents, during the 'window of susceptibility'. Therapy targeted at blocking excitotoxic cell death has not successfully transferred from rodent models of stroke to human stroke patients. Restricting leukocyte entry to the brain, thereby inhibiting the inflammatory response, may prove to be a more practical therapeutic approach. The evidence presented in this review suggests that antagonising the effects of CXC chemokines may represent one route to achieve this goal.